COMPARATIVE ELECTROPHORETIC STUDIES OF LENS PROTEIN ISOLATED FROM PUNTIUS TICTO (HAMILTON 1822) AND RASBORA DANICONUS (HAMILTON 1822) - E. R. MARTIN,; S. D. PAGARE, (The Bioscan, 2012)
A comparative electrophoretic study of the eyelens protein of two freshwater fishes viz. Puntius ticto and Rasbora daniconus was carried out. Electrophoretic analyses revealed substantial differences in the polypeptide distribu- tion in both the fishes. SDS-PAGE of water soluble fractions of lens protein showed several bands ranging from 70-13.5 kDa and 74-13.5 kDa in P. ticto and R. daniconus respectively. The insoluble protein fraction was further resolved into the urea soluble lens protein (USLP) and plasma membrane protein fraction(PMP), SDS-PAGE analysis of the USLP fraction showed the presence of 6 bands ranging from 120-13.5 kDa in P. ticto and 114- 13,5 kDa in R. daniconus The PMP fraction of P. ticto resolved into 6 subunits ranging from 74-13.5 kDa. In contrast only two bands corresponding to 29 and 13.5 KDa was observed for the PMP fraction of R. daniconus . The present study demonstrates a complete variation in the protein pattern of the soluble and insoluble protein fraction in these two fishes. The variation in eye lens protein which are considered to be a conserved protein suggest that the R. daniconus had undergone gene duplication in the course of evolution and the two fishes may have evolved differently.